Du rôle des relations humaines dans la Recherche en général et de celui de Bartolomé Bennassar dans la recherche sur l’Inquisition en particulier - Jean-Pierre Dedieu (Les Cahiers de Framespa)
On reasearch as a personal commitment. Bennassar’s part in the relational interplay which sustained inquisitorial studies. Reasearch is not a mere professional activity. It requires a personal commitment of the researcher. Bartolomé Bennassar was a master in eliciting such a commitment from his students and collaborators.